PERSEPSI MASYARAKAT TERHADAP PEREMPUAN YANG BEKERJA SEBAGAI LC (LADY COMPANION) DI NANGA PINOH KALIMANTAN BARAT KABUPATEN MELAWI - Dea Septiana Nawang; Stela Kaladurisa; Syarifah Rahma Samara; Dahniar TH Musa; Annisa Rizqa Alamri (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2023)
The world of night entertainment is in great demand by today's society, one of which is Karaoke. In karaoke places, you must have a LC (lady companion) whose role is as a companion to accompany customers and entertain them in singing. It is this role that makes most people view the work of LC (lady companion) as not in accordance with the norms prevailing in society. This research is an ethnographic paper and the approach used in this research is a qualitative approach where this research is carried out with a series of processes through field observations, in-depth interviews with informants and documentation by taking photographs as supporting evidence in the field. Social construction theory Peter L. Berger and Thomas Luckman is used to dissect the phenomena in this study. This research is a socio-cultural study that is oriented towards people's personality which often has negative stereotypes for LC (lady companion) workers, especially gender anthropology who studies the role of women who work for their survival. The results of this study indicate that there is a negative stigma on LC (lady companion) workers such as being considered a woman incorrectly because her role in her work is inconsistent with the values ​​of community life. in the Karaoke Romeo environment, on Jalan Sudimulyo, Melawi Regency, West Kalimantan as a study of cultural phenomena. This study aims to find out how the community views LC (lady companion) supervisors and the reasons women do LC (lady companion) work.